Integration of virtual network functions and physical network functions - Bacelo, João Manuel Alves de Mesquita (2021)
Network Functions Virtualization (NFV) and Software Defined Networking (SDN) have been in the center of network evolution, promising a more flexible and efficient way of managing networks through the on-demand instantiation of network functions (NFs) and reconfigurability of the network as necessary. Nevertheless, as new mechanisms are developed, such technologies require testing before their adoption into real-world deployments. This is where this dissertation contributes, by proposing and evaluating a system architecture that integrates a physical wireless testbed with a cloud-based environment. This allows physical wireless nodes to become part of the cloud environment, enabling its use and configuration as virtual NFs (VNFs). Results showcased the system feasibility, with the testbed being able to instantiate on-demand virtual and physical NFs, in the physical wireless nodes and in an OpenStack data-center.